The effect of maritime English vocabulary for beginners module on the vocabulary learning outcomes - Mochamad Abduh; Juliandri Hasnur; Syafni Yelvi Siska (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2022)
This research started from the problem of the current Covid-19 pandemic condition and situation, which makes cadets have to study online and most by themselves. In addition, it is based on the fact that there has been no specific module discussing basic terms or maritime English vocabulary specifically for each department. The purpose of this study is to reveal whether there is an effect of using the maritime English vocabulary for beginners module on the vocabulary learning outcomes and how effective the use of the module is for cadets of Batch V Nautical Department, Shipping Polytechnic, West Sumatra. This type of research is experimental with the one-group pre-test and post-test design (pre-experimental design). This research was carried out in all classes of the nautical department Batch V, which consisted of 3 categories; Nautical A, Nautical B, and Nautical C. The sample used purposive sampling in this research, so the writer only took cadets in nautical majors, with a total sample of 60 persons. Based on the results, it was found that there was an effect of using the maritime English vocabulary for beginners module on the learning outcomes of maritime English vocabulary for Nautical Department cadets Batch V. Furthermore, from the results of questionnaire data processing, it can be concluded that the use of maritime English vocabulary for beginners module in maritime English vocabulary learning is effective for Nautical Department cadets Batch V in West Sumatra Merchant Marine Polytechnic in 2021.